ANALYSIS OF IMPERFECTION OF MATHEMATICAL IDENTITY IN PROBLEM-SOLVING - Fatqurhohman, Fatqurhohman; Firdaus, Hana Puspita Eka (IAIN Ambon, 2024)
The discrepancy between students' strong mathematical identity and their academic performance indicates that contextual and cognitive factors play a role in influencing their problem-solving abilities in mathematics. This study aims to analyze the impact of imperfect mathematical identity on students' ability to solve mathematical problems. Using a qualitative approach with a case study method, this research involves eighth-grade students from SMP Muhammadiyah 7 Jember who have a strong mathematical identity but low academic achievement. Data were collected through surveys, performance tests, and interviews. The findings reveal a mismatch between the high mathematical identity (73%) and low academic performance, particularly in the dimensions of competence (56%) and performance (59%). Additionally, the study shows that low self-confidence, uncertainty in choosing strategies, and limitations in applying effective approaches hinder students' academic achievement. Therefore, this research emphasizes the importance of teachers' roles in developing students' practical skills and implementing concept-based, systematic approaches to enhance problem-solving abilities. It calls for a flexible learning approach, reflective techniques to correct errors, and problem-based learning relevant to real-life situations. Further research is needed to design more effective interventions to support the development of students' mathematical identity. Keywords: Mathematical Identity Imperfection; Mathematical Problem Solving; Learning Reflection; Mathematical Competence; Case Study